Aligning strategic human resource management and person–environment fit - Werbel, James D.; DeMarie, Samuel M. (Human resource management review, 2005)
Strategic human resource management addresses the need to create vertical linkages of human resource management (HRM) attributes with corporate strategy as well as horizontal linkages that integrate practices among HRM functions. Most models commonly focus on either vertical or horizontal linkages. This paper utilizes three categories of person–environment fit to create both vertical and horizontal linkages. Based on a strategic contingency framework, it demonstrates how person–environment fit relates to organizational competencies that supports corporate strategy. Furthermore, it demonstrates how person–environment fit can be used to promote internal alignment of HRM practices. Implications of this approach to strategic human resource management are then discussed.